2019
DOI: 10.1177/0143624419894803
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of cooling jets on the wind and thermal environment in football stadiums in hot climates

Abstract: After winning the bid of the FIFA’s World Cup 2022, Qatar is facing the greatest challenges in terms of minimizing substantial energy consumptions for air-conditioning of stadiums and maintaining aero-thermal comfort for both players and spectators inside stadiums. This paper presents the results of temperature distributions and wind environment of the original stadium under the hot-humid climate and improvements on them for optimized scenarios of cooling jets. A combined computational fluid dynamics and build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…poor resource sharing, weak flexibility of response and slow transmission of information, and instability of aero-thermal comfort, which are considerable affecting the end-users’ experience and restricting the development of sport venues (Zhong et al. 2020 ). To that end, a great attention has been put recently to design intelligent BAMS architectures of sport centers.…”
Section: Overview Of Ai-big Data Analytic Frameworkmentioning
confidence: 99%
“…poor resource sharing, weak flexibility of response and slow transmission of information, and instability of aero-thermal comfort, which are considerable affecting the end-users’ experience and restricting the development of sport venues (Zhong et al. 2020 ). To that end, a great attention has been put recently to design intelligent BAMS architectures of sport centers.…”
Section: Overview Of Ai-big Data Analytic Frameworkmentioning
confidence: 99%
“…More recently, the work carried out by Zhong, Calautit, and Hughes [21] also explored the influence of the positioning of the air cooling jets on the ventilation and thermal performance of stadiums in hot climates but considered the entire stadium bowl. The study attempted to address the issue observed by [16] regarding the uneven airflow velocity and temperature distribution around the spectators' tiers and the center of the pitch.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The study showed an optimum temperature distribution and air circulation pattern for the scenario using cooling jets with a supply velocity of 5 to 25 m/s and supply temperature of 18 • C above the tiers and radiant cooling pipes. Zhong et al [19] explored the temperature distributions and wind flow conditions for a case study stadium without and with cooling jets under the hot-humid climate of Qatar and presented comparisons of three cooling jets configurations: (1) vertical jets above the upper tiers only, (2) combined vertical and horizontal jets at tiers with only an array of jets around the pitch, (3) combined vertical and horizontal jets at tiers with three arrays of jets around the pitch. The results showed that the third configuration performed best among the three configurations.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The air curtain, defined as a continuous air stream projected over the entire envelop openings, which prevents the penetration of unconditioned air to the indoor conditioned spaces [20], has the potential to solve the limitation presented in the previous study of Zhong et al [19]. It is typically used to block smoke from fires for buildings [21] and to provide heat and moisture insulation for refrigerated storages [22,23].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation